2003
DOI: 10.1007/s10072-003-0147-6
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors of multiple sclerosis: a case-control study

Abstract: We assessed the risk of multiple sclerosis (MS) associated with a series of putative risk factors. We studied 140 patients (90 women) with MS (mean age, 42.1 years; SD= 10.2 years; disease duration, 10.9 years, SD= 7.5 years) and 131 sex-and age-matched controls. Using a structured questionnaire, we collected information related to demographic data, socio-economic status, education, ethnicity, changes of domiciles, migration, occupation, environmental, nutritional and hormonal factors, exposure to various bact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
96
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(110 citation statements)
references
References 33 publications
11
96
0
Order By: Relevance
“…Several studies have indicated an association between genetic factors and the risk of MS (1,30,31). Zor-zon (2003) suggested that family history is a significant risk factor for MS (32), consistent with the findings of the present study. These results suggest a role for genetic susceptibility in the risk of MS.…”
Section: Discussionsupporting
confidence: 91%
“…Several studies have indicated an association between genetic factors and the risk of MS (1,30,31). Zor-zon (2003) suggested that family history is a significant risk factor for MS (32), consistent with the findings of the present study. These results suggest a role for genetic susceptibility in the risk of MS.…”
Section: Discussionsupporting
confidence: 91%
“…Ghadirian et al 9 , Zorzon et al 27 and Riise et al 17 also reported a direct and statistically signficant relationship between smoking and MS. Tardieu and Mikaeloff 29 also have shown that the risk of MS was increased by passive smoking at home, but this aspect was not studied in the current work.…”
Section: Resultsmentioning
confidence: 92%
“…Moreover, there was no difference between cases and controls with respect to race / ethnicity or education level. MS has been reported to become clinical apparent or be exacerbated following immunization with a variety of vaccines 9,15,27 . In the meantime, in a recent systematic review conducted by Hernán, Alonso and Hernández-Díaz 28 the OR of MS associated with history of tetanus vaccination was 0.67 (95% CI: 0.55 to 0.81).…”
Section: Resultsmentioning
confidence: 99%
“…Similar results were also observed in Vecca and Nicoletti's studies. [10][11][12] In the study by Putzki, female to male ratio was 2.13 to 1. Corresponding to above mentioned studies, the women in the present study constituted the majority of people with MS (73.13%).…”
Section: Discussionmentioning
confidence: 93%
“…1,2,6,[8][9][10][11] In a study undertaken by Ashtary, 76% of patients with MS were female. 9 Similarly, in Ashtiani's study, 76.9% of patients with MS were female.…”
Section: Discussionmentioning
confidence: 99%